2010
DOI: 10.1007/s11270-010-0383-3
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Chromium Alter Life Cycle Variables and the Equiproportional Development of the Freshwater Copepod Notodiaptomus conifer (SARS)

Abstract: Recent studies have shown that the lower basin of the Salado River is highly polluted with copper and chromium. In order to evaluate the effect of those metals on Notodiaptomus conifer, a representative calanoid copepod, we carried out two (acute and chronic) experimental assays. In the first one, the 24-and 48-h EC 50 values were determined in nauplii and adults. Chronic assays were conducted to evaluate the time of development for nauplii, time of development for each copepodite stage, total development time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…These concentrations were subsequently used to benchmark copper spiked experimental seawater. 1 ml of a copper stock solution (330 mg CuSO 4 L −1 in Milli-Q water) was added to 6 L of filtered natural seawater (salinity 36, collected Tyne estuary, UK); CuSO 4 is often used in copper toxicity testing [39], [49]. Addition of the pore water spike to natural seawater (copper) at 14 µg L −1 gave a final concentration of 20 µg L −1 .…”
Section: Methodsmentioning
confidence: 99%
“…These concentrations were subsequently used to benchmark copper spiked experimental seawater. 1 ml of a copper stock solution (330 mg CuSO 4 L −1 in Milli-Q water) was added to 6 L of filtered natural seawater (salinity 36, collected Tyne estuary, UK); CuSO 4 is often used in copper toxicity testing [39], [49]. Addition of the pore water spike to natural seawater (copper) at 14 µg L −1 gave a final concentration of 20 µg L −1 .…”
Section: Methodsmentioning
confidence: 99%
“…As high metabolic rates are expected to increase the influx rate of toxicants in aquatic crustaceans [27,44,56], the invariability of the SRRs between 14 and 17 • C may be considered protective to this species. In addition, the absence of SRR variability suggests that the survival of D. belgicus at a temperature of 1.1 • C above the highest measured in the Medio Valdarno porous aquifer does not depend on the ability of this species to satisfy its aerobic metabolic demand [57].…”
Section: Discussionmentioning
confidence: 99%
“…De Schamphelaere et al (2007) reported delays in the first reproduction (12 th day of exposure), besides other effects after the first brood was released, when D. magna was exposed to this metal. On the other hand, Gutierrez et al (2010) observed a change in the life cycle, in fertility and in the formation of the first egg sac of the copepode Notodiaptomus conifer (SARS) exposed to copper. Wang et al (2007), using the same metal (Cu), observed a progressive reduction in the size beginning with the second brood of Moina monogolica Daday.…”
Section: Discussionmentioning
confidence: 99%